Assessment of the role of the Public Health Midwife in the delivery of Primary Health Care. - De Silva, D..S (My University, 1991)
This study was carried out in RDHS division, Galle in 1988.The work performance of the study sample was assessed and the relationship of the work performance to demographic,socio economic ,service experience and service facilities of the public health midwife was analyzed. The age of the public health midwife had no significant effect on her work performance. The public health midwife classified in the social class 4 5 score significantly higher in the performance of immunization and talquist's test. Educational level of the public health midwife had no significant association to work performance. The service experience or the service period in the present station of the public health midwife did not demonstrate any significant difference in work performance except, the number of untrained deliveries and the average birth weight in the area. Considering the civil disturbances prevailed in the country during the study period and the limited facilities the performance of the public health midwife was satisfactory. Provision of achievable targets, organized supervision, manageable population and incentive for field work may improve the performance thus enabling the country to reach the goal of health for all by the year by 2000